2018
DOI: 10.21935/tls.v1i2.95
|View full text |Cite
|
Sign up to set email alerts
|

Tailored Fiber Placement in Thermoplastic Composites

Abstract: Fiber path optimization methods combined with the Tailor Fiber Placement (TFP) technology provide the optimum correlation between load case and fiber orientation and therefore lead to unmatched component performance with endless fiber composite materials. The aim of this work is the development of an innovative manufacturing technology for thermoplastic composites (TPC) including sizing-adapted commingled glass fiber (GF) / thermoplastic yarns (SpinCom yarns) to be processed by TFP to textile preforms with a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…While most of the studies use thermoset composites in TFP, applications of thermoplastics are also investigated. 49,50 The TFP process has a relatively faster rate of tow deposition, but smaller width of the tows takes longer to manufacture complex geometries.…”
Section: Manufacturing Of Variable Stiffness Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…While most of the studies use thermoset composites in TFP, applications of thermoplastics are also investigated. 49,50 The TFP process has a relatively faster rate of tow deposition, but smaller width of the tows takes longer to manufacture complex geometries.…”
Section: Manufacturing Of Variable Stiffness Compositesmentioning
confidence: 99%
“…While most of the studies use thermoset composites in TFP, applications of thermoplastics are also investigated. 49,50 The TFP process has a relatively faster rate of tow deposition, but smaller width of the tows takes longer to manufacture complex geometries. Some works also present on the embroidery-based approach with electrodeposition resin molding 51,52 for uniform impregnation of resin.…”
Section: Tailored Fiber Placement Techniquementioning
confidence: 99%
“…Speckenheuer et al presented the first results of research on the possibility of using hybrid threads for the manufacture of tfp-preforms, allowing to obtain high-quality composites. The commingled yarns are made by simultaneous spinning of E-glass fibers (GF) and Polybutylenterephthalat (PBT) filaments with different sizings and have increased adhesion to the matrix [31]. Thus, it should be noted that currently TFP technology applies standard threads used in the textile and chemical industries.…”
Section: Stitching Threads For Tfp-preformsmentioning
confidence: 99%
“…No significant increase in the impact strength was observed. In paper [31], SpinCom hybrid threads [33] consisting of glass and polybutylene terephthalate fibers were used to produceTFP preforms of thermoplastic composite samples. The possible use of hybrid threads to produce thermoplastic composites based on TFP preformswas demonstratedon the example of a bicycle saddle.The test results showed that the combination of the size-adapted SpinCom combination yarn and the Tailored Fiber Placement technology allows to obtain high-quality thermoplastic composites with the precise location and efficient use of the material.…”
Section: Physical and Mechanical Properties Of Stitched Reinforced Plmentioning
confidence: 99%
See 1 more Smart Citation